Riset Tentang Manajemen Pendidikan Islam - Oktawira, Leni; Apriyenti, Apriyenti; Rahmawati, Aulia; Rinny S; Hidayat, Rahmad (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine the implementation of research in Islamic Education Management. This study uses a literature review approach to explore various dimensions of research in Islamic education management. The research method involves the systematic identification, analysis, and synthesis of credible scientific articles, books, and academic sources related to the topic. Major databases such as Google Scholar are used to collect relevant literature published in the last decade. The selection criteria include research that discusses theoretical frameworks, practical applications, and contemporary research challenges in Islamic education management. These sources are evaluated based on their academic rigor, relevance, and contributions to the field. The results of the analysis show that the research process in Islamic education management includes several important stages, namely research planning, data collection, data analysis, and reporting results. The study highlights the important role of effective management in advancing the quality and sustainability of Islamic education. Through a comprehensive literature review, it was found that key aspects such as leadership, curriculum design, resource management, and policy implementation are fundamental to the success of Islamic educational institutions. This research contributes to existing knowledge by synthesizing insights from various sources and offers a foundation for future research